Targeting Krasg12c‐mutant cancer with a mutation‐specific inhibitor. (7th April 2020) - Christensen, J. G.; Olson, P.; Briere, T.; Wiel, C.; Bergo, M. O.
Abstract: The RAS genes, which include H, N, and KRAS, comprise the most frequently mutated family of oncogenes in cancer. Mutations in KRAS – such as the G12C mutation – are found in most pancreatic, half of colorectal and a third of lung cancer cases and is thus responsible for a substantial proportion of cancer deaths. Consequently, KRAS has been the subject of exhaustive drug‐targeting efforts over the past 3–4 decades. These efforts have included targeting the KRAS protein itself but also its posttranslational modifications, membrane localization, protein–protein interactions and downstream signalling pathways. Most of these strategies have failed and no KRAS‐specific drugs have yet been approved. However, for one specific mutation, KRAS G12C, there is light on the horizon. MRTX849 was recently identified as a potent, selective and covalent KRAS G12C inhibitor that possesses favourable drug‐like properties. MRTX849 selectively modifies the mutant cysteine residue in GDP‐bound KRAS G12C and inhibits GTP‐loading and downstream KRAS‐dependent signalling. The drug inhibits the in vivo growth of multiple KRAS G12C ‐mutant cell line xenografts, causes tumour regression in patient‐derived xenograft models and shows striking responses in combination with other agents. It has also produced objective responses in patients with mutant‐specific lung and colorectal cancer. In this review, we discuss the history of RAS drug‐targeting efforts, the discovery of MRTX849, and how this drug provides an exciting and long‐awaited opportunity to selectively target mutant KRAS in patients. Abstract :